2013
DOI: 10.1007/s13437-013-0037-6
|View full text |Cite
|
Sign up to set email alerts
|

Sexual risk among female workers on cruise ships

Abstract: Data were combined from two studies-qualitative interviews with 19 female cruise-ship workers in a Florida port and 192 quantitative interviews conducted with male and female cruise-ship workers in a European and a Florida port. High rates of partner change were reported in the latter sample: 39 % reported two or more sexual partners in the past year. Logistic regression analysis of 16 different variables showed that gender was the variable most strongly independently associated with a new sexual relationship:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…On their return from that first sea training, approximately one in six reported experiencing (or witnessing the experience of) sexual harassment. This is consistent with earlier findings, which suggest that sexual harassment of female seafarers by male crew is commonplace (Thomas et al., 2013) and indicates worryingly little progress over time. Relatedly, and of even more concern, representatives of stakeholders from across the industry indicated that this was the norm and it was the widely held view that all women who remained and progressed in the industry would have experienced sexual harassment at least once in their working lives.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On their return from that first sea training, approximately one in six reported experiencing (or witnessing the experience of) sexual harassment. This is consistent with earlier findings, which suggest that sexual harassment of female seafarers by male crew is commonplace (Thomas et al., 2013) and indicates worryingly little progress over time. Relatedly, and of even more concern, representatives of stakeholders from across the industry indicated that this was the norm and it was the widely held view that all women who remained and progressed in the industry would have experienced sexual harassment at least once in their working lives.…”
Section: Discussionsupporting
confidence: 92%
“…These figures perpetuate the difficulties of recruiting women into an industry that lacks female role models, especially in higher ranks (Kitada, 2013; Mackenzie, 2015). The industry is often seen as unattractive to women (IMO, 2019) and has been recognised as one in which the lived, workplace experiences of women often fall short of those of their male counterparts and can include prejudice, discrimination and harassment (Sampson, 2013; Thomas et al., 2013; Acejo and Abila, 2016). As Kitada and Langåker (2017) make clear, being part of a minority group can be challenging, both for the individual and for the wider industry.…”
Section: Introductionmentioning
confidence: 99%
“…According to some research, STIs do not pose a significant problem on cruise or merchant navy ships (Schlaich et al, 2009). A study by Thomas et al indicates that female workers on cruise ships have a greater tendency of changing sex partners while on board than men (Thomas et al, 2013). It seems that cruise ship workers represent a potentially important group for understanding and combating the spread of sexually transmitted infections.…”
Section: Sexually Transmitted Infectionsmentioning
confidence: 99%
“…It seems that cruise ship workers represent a potentially important group for understanding and combating the spread of sexually transmitted infections. Migrant workers in general, and seafarers in particular, have long been acknowledged to be both vulnerable to sexually transmitted infections and they are an important factor of sexually diseases spread in different, especially domicile populations (Gershman et al, 2020;Pougnet et al, 2020;Mulic et al, 2010;Thomas et al, 2013).…”
Section: Sexually Transmitted Infectionsmentioning
confidence: 99%